2021
DOI: 10.1080/03004279.2021.1960579
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and remote learning: experiences of parents supporting children with special needs and disability during the pandemic

Abstract: Citing this article.Patricia A. Shaw & Alan Shaw (2021) COVID-19 and remote learning: experiences of parents supporting children with special needs and disability during the pandemic, Education 3-13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…The COVID-19 pandemic is unique in that access to schooling can be remote, which may or may not offer similar opportunities, and indeed may create additional stresses in a household, for example, in the need to supervise remote learning. Facilitating access to remote schooling requires equipping educational systems with tools to be able to better deliver remote schooling such as providing training to improve "digital competence" among teachers and students, implementing routines to promote closer partnership between teachers and caregivers, and sharing higher-quality and tailored resources along with more guidance on routines [59] for vulnerable students who may face additional barriers [60].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic is unique in that access to schooling can be remote, which may or may not offer similar opportunities, and indeed may create additional stresses in a household, for example, in the need to supervise remote learning. Facilitating access to remote schooling requires equipping educational systems with tools to be able to better deliver remote schooling such as providing training to improve "digital competence" among teachers and students, implementing routines to promote closer partnership between teachers and caregivers, and sharing higher-quality and tailored resources along with more guidance on routines [59] for vulnerable students who may face additional barriers [60].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have indicated that implementing remote education was particularly difficult for students with autism, who require a high level of routine and regularity [ 19 ]. A number of studies focusing on parents of children with SEN have found a lack of appropriate materials and resources tailored to the needs of these students and the need for the parent to step into the role of expert specialist, despite a lack of competence in this area [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research from Shaw and Shaw (2021) identified several themes from a qualitative questionnaire with 137 parents of TD and DD school-aged children (i.e., 4-18 years old) from the United Kingdom who had taken a primary role in their child's educational activities. The themes include a perceived lack of ability to educate their child effectively at home, a change in family dynamics as a result of the dual role (caregiver & education professional substitute), and the need for a routine in order to address emotional needs (Shaw & Shaw, 2021). Research has also indicated that despite agreeing with in-person school closures, parents struggled with motivating their child to engage in educational activities and the production of satisfactory learning outcomes and socio-emotional development (Garbe et al, 2020).…”
Section: The Impact On Parents and Caregiversmentioning
confidence: 99%
“…While the impact of school closures and increased demands for parent involvement in educational activities is still emerging, research to date has produced mixed results. Research from Shaw and Shaw (2021) identified several themes from a qualitative questionnaire with 137 parents of TD and DD school-aged children (i.e., 4–18 years old) from the United Kingdom who had taken a primary role in their child's educational activities. The themes include a perceived lack of ability to educate their child effectively at home, a change in family dynamics as a result of the dual role (caregiver & education professional substitute), and the need for a routine in order to address emotional needs (Shaw & Shaw, 2021).…”
Section: The Impact On Parents and Caregiversmentioning
confidence: 99%